2018
DOI: 10.1002/cncr.31798
|View full text |Cite
|
Sign up to set email alerts
|

Risk of incident claims for chemotherapy‐induced peripheral neuropathy among women with breast cancer in a Medicare population

Abstract: Background Chemotherapy‐induced peripheral neuropathy (CIPN) is a common and disabling consequence of neurotoxic therapies, yet factors that modulate the development and clinical impact of CIPN are poorly understood. This epidemiological analysis identifies risk factors for the incidence of CIPN. Methods This retrospective analysis of Surveillance, Epidemiology, and End Results–Medicare data examined predictors of incident CIPN claims among 11,149 women aged 66 years or older with American Joint Commission on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 28 publications
1
13
1
Order By: Relevance
“…Some studies identified more severe TIPN in African‐American women with breast cancer, with some studies identifying race as the most significant TIPN predictor . However, this has not held in all studies, with no significant risk of TIPN by race in a multi‐cancer cohort aged >65 years or in a breast cancer cohort …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies identified more severe TIPN in African‐American women with breast cancer, with some studies identifying race as the most significant TIPN predictor . However, this has not held in all studies, with no significant risk of TIPN by race in a multi‐cancer cohort aged >65 years or in a breast cancer cohort …”
Section: Introductionmentioning
confidence: 99%
“…Similarly, pre‐existing neuropathy was a risk factor for TIPN in some studies but not others . Large‐scale population‐based studies have not identified an association between pre‐existing neuropathy or diabetes and TIPN, but the identification of neuropathy was based on retrospective review of medical notes, which is likely to result in underestimation.…”
Section: Introductionmentioning
confidence: 99%
“…Chemotherapy-induced peripheral neuropathy (PN) refers to a progressive, persistent, and sometimes irreversible condition that affects approximately 30–40% of patients with BC receiving chemotherapy, including paclitaxel, docetaxel, cisplatin, carboplatin, bortezomib, or vincristine [ 213 , 214 ]. This condition provokes structural deficits in Dorsal Root Ganglia, affecting sensory neurons in this region, satellite cells, Schwann cells, as well as neuronal and glial cells in the spinal cord.…”
Section: Pa In Bc Managementmentioning
confidence: 99%
“…Previously implicated risk factors for CIPN that have been consistently observed across studies include pre-existing or early-onset symptoms of neuropathy (e.g., [10][11][12][13][14]), anxiety or depression (e.g., [13,15]), and sedentary behavior (e.g., [16][17][18]); for a review see [2]. Some risk factors inconsistently observed across studies include older age (e.g., null ndings in [10][11][12]19]; positive ndings in [16,20]; opposite trend in [21]) and diabetes status (e.g., null ndings in [12,22,23]; positive ndings in [24]).…”
Section: Introductionmentioning
confidence: 99%